2021
DOI: 10.5009/gnl20270
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Slow Pull versus Suction for Endoscopic Ultrasound-Guided Tissue Acquisition

Abstract: Background/Aims: Endoscopic ultrasound (EUS)-guided tissue acquisition is widely utilized as a diagnostic modality for intra-abdominal masses, but there remains debate regarding which suction technique, slow pull (SP) or conventional suction (CS), is better. A meta-analysis of reported studies was conducted to compare the diagnostic yields of SP and CS during EUS-guided tissue acquisition. Methods: We conducted a systematic electronic search using MEDLINE/PubMed, Web of Science, and the Cochrane Central Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Recent FNB needles have various features to increase cellularity of the specimen, and the resistance at needle advancement should be evaluated in these new FNB needles. We previously reported the slow pull method was associated with the better diagnostic yield in a 25‐gauge FNA needle 50 and FNB needles 51 . Although the use of slow pull method was not associated with the better diagnostic yield in our meta‐analysis, the best suction technique for small SPLs remains to be clarified.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Recent FNB needles have various features to increase cellularity of the specimen, and the resistance at needle advancement should be evaluated in these new FNB needles. We previously reported the slow pull method was associated with the better diagnostic yield in a 25‐gauge FNA needle 50 and FNB needles 51 . Although the use of slow pull method was not associated with the better diagnostic yield in our meta‐analysis, the best suction technique for small SPLs remains to be clarified.…”
Section: Introductionmentioning
confidence: 65%
“…We previously reported the slow pull method was associated with the better diagnostic yield in a 25‐gauge FNA needle 50 and FNB needles. 51 Although the use of slow pull method was not associated with the better diagnostic yield in our meta‐analysis, the best suction technique for small SPLs remains to be clarified.…”
Section: Introductionmentioning
confidence: 78%
“…A previous meta-analysis by Nakai et al [8] reported that SSP was likely to provide lower blood contamination but similar cellularity and diagnostic accuracy compared to DS. However, ran-domized trials, studies using 25G needle and studies involving pancreatic lesions showed higher diagnostic accuracy with SSP than DS on sensitivity analysis.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, many reports suggest the absence of any significant difference in the diagnostic performance between the two techniques [ 65 , 66 , 67 , 68 , 69 , 70 ]. One meta-analysis concluded that, although there was no difference in the accuracy or sensitivity between the two techniques, use of the non-suction technique was associated with a significantly lower rate of blood contamination compared to use of the conventional suction technique [ 71 ].…”
Section: Endoscopic Ultrasound-guided Tissue Acquisition (Eus-ta)mentioning
confidence: 99%